CONTENTS OF THE EUROPEAN CLASSICAL MODEL OF ACADEMIC AND FINANCIAL AUTONOMY PRINCIPLES - Azamov Jasur (Scholar Express Journal, 2022)
The article analyzes the views on the structure of governing bodies of higher education institutions in Europe in assessing the level of organizational independence and institutional capacity. Opinions are given on the activities of the decision-making body and advisory bodies, which are the main governing bodies of higher education
Keywords: Academic Autonomy; Financial Autonomy; Institutional Autonomy; Education Management